MolArt: a molecular structure annotation and visualization tool - Hoksza, David; Gawron, Piotr; Ostaszewski, Marek; Schneider, Reinhard (Bioinformatics, 2018)
Summary: MolArt fills the gap between sequence and structure visualization by providing a light-weight, interactive environment enabling exploration of sequence annotations in the context of available experimental or predicted protein structures. Provided a UniProt ID, MolArt downloads and displays sequence annotations, sequence-structure mapping and relevant structures. The sequence and structure views are interlinked, enabling sequence annotations being color overlaid over the mapped structures, thus providing an enhanced understanding and interpretation of the available molecular data. Availability and implementation: MolArt is released under the Apache 2 license and is available at https://github.com/davidhoksza/MolArt. The project web page https://davidhoksza.github.io/MolArt/ features examples and applications of the tool.
Keywords: konformace proteinů; Software; Molecular Structure; software; molekulární struktura; Computational Biology; Proteins; proteiny; Protein Conformation; výpočetní biologie; barva; Color